Perspectives on aesthetics and vulnerability through the life stories of five young men - Møller-Skau, Marie (FormAkademisk, 2021)
This article examines what five young men in vulnerable positions tell about their experiences with aesthetics and actualises aesthetics in the context of health and life skills, emphasised in the Norwegian curriculum (2020). For research purposes, an interview with an indirect approach is used to gain insights into these young men’s experiences and lives by allowing them to fully play the roles as storytellers. According to the young men’s stories, their experiences with aesthetics can be presented through three categories of findings: (1) the connection between their life situations and aesthetics, (2) their emotional moments of aesthetic experiences and (3) their experiences of aesthetics as meaningful phenomena. Furthermore, the findings are discussed against aesthetic theory, which highlights how emotions can be experienced, reflected, symbolised, expressed and sorted out through aesthetics. Thus, a picture of aesthetic experiences is drawn as emotional processes.